A CFD study of particle–bubble collision efficiency in froth flotation. (September 2019) - Li, Shuofu; Schwarz, M. Philip; Feng, Yuqing; Witt, Peter; Sun, Chunbao
Highlights: CFD model of bubble-particle collision to determine collision efficiency. Results compared with Schulze and GSE models. Schulze model is in reasonable agreement with CFD results. GSE model overestimates the centrifugal inertial effect. Schulze model should be used as sub-model in macro-scale flotation models. Abstract: To improve understanding of the interaction between bubbles and particles during the flotation process, the interaction between the various factors that affect the collision efficiency has been analyzed in this paper. Four kinds of mineral particles (quartz, chalcopyrite, copper sulfide and galena) were investigated. Particle–bubble collisions between bubbles with size ranging from 0.6 mm to 2.0 mm and particles with diameter from 31 μm to 150 μm were examined. Representative analytical mathematical models (Generalised Sutherland Equation (GSE) model and Schulze model) are studied in depth, and errors in the equations for the GSE model reported in a review paper are corrected. Simultaneously, a computational fluid mechanics (CFD) technique was used to establish a fluid mechanics model which can directly reflect the relative motion of bubbles and particles during flotation. The results of the CFD model are compared with the existing mathematical models to analyze the advantages and disadvantages of the existing models as a description of collisions in the flotation process. The GSE model accounts for the centrifugal inertial effect (neglected in the Schulze model), but comparison with the CFD results suggests that it greatly over-estimates this effect. On the other hand, the Schulze model appears to overestimate the collision efficiency at the larger particle size range, giving values greater than unity in some cases. It would be expected that the CFD model would be more exact than either semi-theoretical model, given that it involves fewer assumptions. Therefore, it is recommended that the Schulze model (limited to a value less than unity) should be used as a sub-model for bubble–particle collision rate in macro-scale CFD models of flotation cells rather than the GSE model.